Using Chaotic Lasers to Encrypt Data. - Paulson, Linda Dailey (Computer (00189162), 2006)
The article provides information on the processing of an encrypted information through the fiber-optic lines that emits fluctuating signals. The system, which was discovered by researcher Claudio Mirasso, uses a semiconductor laser. The information is sent over a fiber optic lines by slipping data streams into a laser beam, generating a new signal that unpredictably fluctuates in amplitude. A modulator then provides a message into the new stream which is unreadable. The sending laser also transmits an initial signal to the intended receiving laser, allowing the receiving laser to generate the same signals. According to Mirasso, the technique could complement software encryption techniques and offer a better security.